PERANAN KELUARGA DALAM PELAKSANAAN PENDIDIKAN AGAMA - Deassy Ariestya Sakhsitha; Annisatun Nasfa Nurmarifah; Elfiana; Mar’atus Sholihah; Hafidzoh Halim; Boby Irawan (STKIP Subang, 2026)
The family is the smallest social unit and serves as the first and primary educational environment for children, particularly in laying the foundations of religious education. This study aims to examine the family’s role in implementing religious education and to identify the factors that influence its effectiveness. The research employs a qualitative approach using a library-based method, reviewing various literature sources, scientific journals, and relevant references on the family’s role in children’s religious education. The findings indicate that parents bear the primary responsibility for instilling the values of faith, morality, and worship from an early age through exemplary behavior, habit formation, and effective communication in daily life. Democratic parenting, a harmonious family environment, and parents’ consistency in practicing religious teachings significantly contribute to the development of children’s religious character. Conversely, limited parental involvement and insufficient religious knowledge within the family may hinder the effectiveness of children’s religious education. This study concludes that the family, especially parents, plays a strategic and irreplaceable role in building children’s spiritual foundation, which will influence their religious attitudes and behaviors in the future. Therefore, continuous awareness and efforts from parents are essential to improve the quality of religious education within the family environment.